Antarctic Moss Multiprotein Bridging Factor 1c Overexpression in Arabidopsis Resulted in Enhanced Tolerance to Salt Stress - Alavilli, Hemasundar; Lee, Hyoungseok; Park, Mira; Lee, Byeong-ha (Frontiers in Plant Science, 2017)
Polytrichastrum alpinum is one of the moss species that survives extreme conditions in Antarctic. In order to explore the functional benefits of moss genetic resources, P. alpinum multiprotein-bridging factor 1c gene (PaMBF1c) was isolated and characterized. The deduced amino acid sequence of PaMBF1c comprises of a multiprotein-bridging factor (MBF1) domain and a helix-turn-helix (HTH) domain. PaMBF1c expression was induced by different abiotic stresses in P. alpinum, implying its roles in stress responses. We overexpressed PaMBF1c in Arabidopsis and analyzed the resulting phenotypes in comparison with wildtype and/or Arabidopsis MBF1c (AtMBF1c) overexpressors. Overexpression of PaMBF1c in Arabidopsis resulted in enhanced tolerance to salt and osmotic stress, as well as to cold and heat stress. More specifically, enhanced salt tolerance was observed in PaMBF1c overexpressors in comparison to wild type but not clearly observable in AtMBF1c overexpressing lines. Thus, these results implicate the evolution of PaMBF1c under salt-enriched Antarctic soil. RNA-Seq profiling of NaCl-treated plants revealed that ten salt-stress inducible genes were already up-regulated in PaMBF1c overexpressing plants even before NaCl treatment. Gene ontology enrichment analysis with salt up-regulated genes in each line uncovered that the terms lipid metabolic process, ion transport, and cellular amino acid biosynthetic process were significantly enriched in PaMBF1c overexpressors. Additionally, gene enrichment analysis with salt down-regulated genes in each line revealed that the enriched categories in wild type were not significantly overrepresented in PaMBF1c overexpressing lines. The up-regulation of several genes only in PaMBF1c overexpressing lines suggest that enhanced salt tolerance in PaMBF1c-OE might involve reactive oxygen species (ROS) detoxification, maintenance of ATP homeostasis, and facilitation of Ca2+ signaling. Interestingly, many salt down-regulated ribosome- and translation-related genes were not down-regulated in PaMBF1c overexpressing lines under salt stress. These differentially regulated genes by PaMBF1c overexpression could contribute to the enhanced tolerance in PaMBF1c overexpressing lines under salt stress.